Decision analytical methods for assessing the efficacy of agroecology interventions - Cory Whitney; Lisa Biber-Freudenberger; Eike Luedeling (CABI Agriculture and Bioscience)
Abstract Given the extensive impact of humans on ecosystems and the uncertainty faced by decision-makers when choosing among alternatives, formal support is required for decision-making in complex agroecological systems. While approaches for producing reliable impact projections accounting for system complexity and uncertainty do exist, decision-makers rarely use them to assess the costs, benefits, and risks of agroecology development. Here, we review the literature and provide an overview of decision theory as a methodology for supporting decision-making in agroecology. We also outline the conceptual relationships between decision analysis methods and agroecology, and examine how decision analysis methods can be applied to support decision-making for agroecological transitions. These methods support decisions based on intended outcomes, explicitly accounting for risks and uncertainty, and help decision-makers determine the appropriateness of agroecological interventions for achieving desired outcomes. International frameworks and national government commitments and funding mechanisms, as well as the private sector, would benefit from making use of decision analysis methods to determine the suitability of agroecology interventions and to support and scale them when appropriate. Graphical Abstract